EFEKTIVITAS KEBIJAKAN PENYUSUNAN SURAT PERTANGGUNGJAWABAN (SPJ) PADA DIVISI KEUANGAN KPU PROVINSI JAWA TIMUR - Darajah, Arini; Tukiman, Tukiman (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Policies in a government agency are also made to respond to the needs and problems faced by the community. In the context of the policy of preparing a Letter of Responsibility (SPJ) in the finance division, the General Elections Commission (KPU) was made to ensure transparency and accountability of KPU financial management. SPJ is an important document used to account for the use of the budget that has been received by the KPU. SPJ must be prepared completely, accurately, and in accordance with applicable regulations. This research uses qualitative research methodology with a descriptive approach method. The results of this study stated that the policy of preparing SPJ in the Financial Division of the KPU of East Java Province has been quite effective, it can be seen from the conformity of the principles of SPJ applied in the Finance Division of the KPU of East Java Province, but in its implementation there are still several things that can be improved to increase the effectiveness of the preparation of SPJ in the Financial Division of the KPU of East Java Province. Keywords: Policy; Effectiveness; SPJ